Molecular Screening Strategy to Identify a Non-invasive Delivery Mechanism for the Treatment of Middle Ear Disorders - Kurabi, Arwa; Cooper, Molly; Spriggs, Meghan; Xu, Yuge; Schaerer, Daniel; Ryan, Allen F. (Frontiers in Medicine, 2020)
Middle ear ailments include a broad range of pathological conditions. Otitis media is the leading middle ear disease of childhood, which incurs significant health care resources in developed countries, and in developing countries causes significant mortality and morbidity. Recurrent and chronic infections of the middle ear lead to the prolonged presence of inflammatory factors and cellular infiltrates resulting in temporary hearing loss. However, long-term alteration of the middle ear space can pose the risk of permanent damage to the delicate ear structures and cause tissue remodeling. For otitis media, treatments include systemic antibiotics and the surgical placement of ventilation tubes in the tympanic membrane, both of which have disadvantages. For cholesteatoma, a destructive colonization of the middle ear by epidermal keratinocytes, surgical removal is the only treatment available. While the etiopathogenesis of middle ear diseases is multifactorial, targeting the biological mechanisms and molecular networks that drive disease development is critical. Yet, a pivotal step in realizing the potential of molecular therapies is development of methods for local drug delivery, since systemic application risks side effects. Utilizing bacteriophage display in the rat, we discovered rare peptides that are able to transit the intact tympanic membrane from the external canal to the middle ear cavity by an active process. An in vitro assay demonstrated that transport occurs across the tympanic membranes of humans, and that the peptides cross the membrane independent of phage. Transport of phage, which are approximately 900 nm in length, suggests that these peptides could noninvasively deliver drug packages or gene therapy vectors into the middle ear.